Exploring young pregnant smokers' experiences with a self-nominated non-smoking buddy - Ronchi, Fiona; Lewis, Lucy; Hauck, Yvonne; Doherty, D. (Churchill Livingstone, 2018)
Introduction psychosocial interventions can increase the proportion of women who stop smoking in pregnancy. There is limited research exploring self-nominated, non-smoking buddy support, to assist young pregnant smokers to quit. Methods this qualitative descriptive study was embedded within a randomised controlled study assisting young (16 to 24 years) pregnant smokers to quit. Women were recruited from two public maternity hospitals in Western Australia. Interviews were performed every two weeks from recruitment to six weeks post birth. The study aim was to explore women's experiences with a self-nominated non-smoking buddy. Thematic analysis was utilised to identify common themes. Findings a total of 204 interviews were performed with 36 women, who had a mean of six interviews, with four conducted in pregnancy and two post birth. Two themes were revealed. The first ‘Challenges of finding the right buddy’ reflected the experiences women had in finding a non-smoking buddy to provide support and encompassed three sub themes; 'The only non-smoker I know', ‘Reluctance to alter the existing relationship' and ‘Limited discussion around expectations of buddy support’. The second theme ‘Sustaining the buddy relationship’ centred on the continuing relationship the woman had with her buddy and encompassed three sub themes; ‘Consistent relationship’, ‘Changeable buddies’ and ‘Unofficial buddies’. Conclusion our findings reveal the complexity of incorporating non–smoking buddy support into smoking cessation programs for young pregnant smokers. The characteristics and social environment of individual women may have the capacity to influence their ability to engage and sustain a relationship with a non-smoking buddy.